Sobre Lukács - a partir de sua interpretação n'A Destruição da Razão - Carneiro, Rogério de Oliveira (Universidade Federal de São Carlos, 2008)
In the Destruction of Reason, from 1953, Georg Lukács plays several thinkers as philosophics idealizers of german way to Hitler. This work has as purpose to show such reading as a mistake. Another moment, through a deviation about the Hungarian author s trajectory, shows also that there is a transformation in the writing style after his convertion on the communist party in 1918, wich emphasires mainly after the thirties, in it s soviet period. On the other hand, shows also that during Lukács last years there is an effort to revise mistakes of the past
Keywords: Szegedi Lukács, György, 1885-1871; Filosofia alemã; Filosofia moderna; Nietzsche, Friedrich Wilhelm, 1844-1900; Schelling, Friedrich Wilhelm Joseph Von, 1775-1854; Schopenhauer, Arthur, 1788-1860; Kierkegaard, Soren Aabye, 1813-1855; Pascal, Blaise, 1623-1662; Lukács; Nietzsche; Schelling; Schopenhauer; Kierkegaard; CIENCIAS HUMANAS::FILOSOFIA